Sensory recovery in medial plantar flaps for posterior heel defects as a guide to rehabilitation regime - Dipankar Mukherjee,; Monali Patole Mukherjee,; Santu Kumar Chejara,; Akshay Kapoor,; Debarati Chattopadhyay, (Asian Journal of Medical Sciences, 2025)
Background: For reconstruction of the foot, a medial plantar flap is used to provide a like-for-like replacement. The problem at present seems to be that there are no objective criteria to guide the rehabilitation regimes of these patients. The arbitrary rule that the patient may begin weight-bearing after 4 weeks of surgery may not be applicable to all patients as the etiology of the defect and time for recovery may differ. Aims and Objectives: The study was conducted with the primary objective of ascertaining the time needed for sensory recovery in the pedicled medial plantar flap. The secondary objective was to identify guidelines regarding weight-bearing on the flap during the recovery period. Materials and Methods: A prospective observational study was done, with the primary objective of recording the time in which sensory recovery occurs in sensate pedicled flaps. In 4 years, 14 patients who underwent medial plantar flap reconstruction were assessed. The sensory outcome of medial plantar flaps was assessed using 2-point discrimination (2PD) of the flap area compared with the heel of the normal leg. Results: Tactile sensation was found to recover within one month, but 100% recovery of pain and temperature sensation took about 6 months. A Mann–Whitney test to compare the 2PD scores of the flap to the normal heel showed them to be comparable at 6 months post-operative. Conclusion: Complete sensory recovery even in a sensate flap can take about 6 months and the patient needs to be counseled regarding using assisted weight-bearing and daily foot examination until that period is complete.